SAS and Elite Forces guide special forces in action : elite forces operations, 1991-2011 / Alexander Stillwell. - Stillwell, Alexander (Lyons Press, 2012)
Narrates key events in recent history of special forces operations around the globe, from the Gulf War through Iraq.